TRANSFORMATION OF THE ARCHITECTURE OF DEPOK CITY CASE: KUKUSAN, MARGONDA, PERUMNAS DEPOK I, AND DEPOK LAMA - Nyoman Teguh Prasidha, I
City as architecture undergo a process of transformation over time. Urbanization and modernization have caused and influenced the transformation of the architecture of the cities in various parts of the world. Depok, a city in the southern side of Jakarta, the capital city of Indonesia, has occurred rapid growth and change in the last five decades. Significant changes were marked since the construction of Depok I National Housing (Perumnas) in the middle of 1970s and the presence of the University of Indonesia campus in 1987. Depok in its progress has met an uncontrolled transformation in its city architecture. The impact arise problems in the quality of its city architecture and the environment. During this time various studies and discussions on architecture of the city and urban transformation. It has not been found deep research about the transformation of the architecture of a city, and more specifically about what happens in this case Depok. This study aims to reveal the processes and patterns of the transformation of the Depok city architecture that have occurred from 1970 to 2020; to describe the factors that affect transformation; to explain how the character of the city was formed; and to reveal the effect of transformation on the quality of the architecture of Depok city. Based on its purpose, this research is a case study with multi cases research, using typo-morphology and historical of city development approach. The research was conducted in four areas that represent the transformation of the architecture of Depok city, i.e. Kukusan, Margonda, Perumnas I Depok, and Depok Lama. The determination is based on the consideration of the phenomenon of rapid city architectural transformation in the area around the university campus, the main corridor of the city, the first residential area in Depok, and an area that has a history of colonial heritage. The results of this study revealed that each area has differences and similarities of the transformation patterns and process of the city architecture. The similarity of the transformation pattern is in the form of division and merging of plots, increasing the area of space and building floor, changing the form and appearance of the building, adding new buildings, changing or adding functions/activities, adding roads, and reducing open space. The difference between the four locations is the typology of transformation of city architecture elements in the area around of the university campus, commuter corridor area, planned mass housing area, and historical area. The transformation of the architecture of Depok city reflects the dynamics of the life of its people, as a result of the influence of various factors. Development policies, economic, social, transportation, historical, and regional are the main factors that influence the city architectural transformation. The processes and patterns of city architectural transformation in the four research areas are influenced by various factors, both external and internal, directly and indirectly. The uncontrolled contestation of spatial use has led to various conflicts and has implications for increasing the area and intensity of the built space, but on the other hand there has been a drastic decrease in open or un-built space. The results of the assessment of changes in the quality of the architecture of Depok city and the factors that influence indicate that the quality of the architecture of Depok city is quite bad with various environmental problems. This research complements the theoretical discourse on the architecture of the city and strengthens the opinion that city architecture is not only related to the visual, aesthetic aspects of the city, or as a criticism of modern architecture, but has developed influenced by various factors of urban life such as politics, economy, social, history, transportation, and regional, which are interrelated and mutually influential. One or several factors can have a more dominant influence on the processes and patterns of the transformation of city architecture, and also affect the character and quality of the city architecture and its environment.